METHODOLOGY OF WORKING WITH HISTORICAL CONCEPTS IN THE STUDY OF ARTISTIC WORKS (Universal International Scientific Journal, 2026)
In this article, we will shed light on the concepts that teaching historical concepts to elementary school students through works of art helps to expand their thinking, form historical memory, and deepen their spiritual and educational education. Through works, students learn to study historical periods, events, and individuals, and analyze their causes and effects. It helps to develop their historical thinking and understand events more deeply.
Keywords: : Historical concept, historical process, primary school, historical period, fiction, visual learning, figurative learning.